Mapping of advanced practice nursing actions in the Family Health Strategy - Emerson Willian Santos de Almeida; Simone de Godoy; Ítalo Rodolfo Silva; Orlene Veloso Dias; Leila Maria Marchi-Alves; Isabel Amélia Costa Mendes (Revista Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to map advanced practice nursing actions implemented in the Family Health Strategy context. Methods: cross-sectional exploratory study carried out with Family Health Strategy nurses. Data obtained in the mapping were compared to the characteristics that define advanced practice nurses and are adopted internationally by using a checklist based on the International Council of Nurses Guidelines. Results: the mapping allowed to identify advanced practice nursing actions, such as advanced assessment, judgement, decision-making, and diagnostic reasoning skills and authority to diagnose and prescribe medications, diagnostic testing, and therapeutic treatments. However, evidence found in the educational preparation domain indicated evident fragility, expressed as the low percentage of nurses credentialed with a professional master’s degree. Conclusions: the present study showed that nurses in the Family Health Strategy carry out advanced practice nursing actions without the professional master’s degree recommended for credentialing, with pertinent legislation, which requires initiatives to be taken by nursing leaders to overcome this deficiency.